Quantum web of trust. Issue 2 (17th November 2021) - Nema, Prashant; Nene, Manisha J.
Abstract: Authentication is the foremost requirement for any online secure transaction. In post quantum era, public key encryption is considered no longer a safe option. The research is therefore, progressing toward providing a quantum resistant solution using both classical as well as quantum computing medium. The paper proposes a quantum based mutual authentication protocol for autonomous system, utilizing the properties of quantum mechanics for exchange, storage and validation of confidential data. The protocol so designed evolves into a chain of mutually trusted nodes to form quantum web of trust. The protocol cater for devices infected with malware by utilizing physically unclonable function inside trusted platform module. The mathematical expressions conveying the correctness of operations has been demonstrated on a quantum machine to verify the efficacy of the protocol. The security analysis demonstrates the ability of the proposed protocol to mitigate cyber attacks and eavesdropping in the network.